A laboratory and simulation study of preformed particle gels for water conformance control. (15th January 2015) - Goudarzi, Ali; Zhang, Hao; Varavei, Abdoljalil; Taksaudom, Pongpak; Hu, Yunpeng; Delshad, Mojdeh; Bai, Baojun; Sepehrnoori, Kamy
Highlights: PPG experiments in both fracture and sandpack were successfully performed. PPG experiments rank the effect of PPG on improving conformance. We have developed mathematical models for gel rheology, adsorption, swelling ratio. The gel transport models were implemented in a reservoir simulator (UTGEL). The UTGEL simulator was validated against laboratory experiments. Abstract: Excess water production is a major problem that leads to early well abandonment and unrecoverable hydrocarbon in mature oil fields. Gel treatments at the injection wells to preferentially plug the thief zones are cost-effective methods to improve sweep efficiency in reservoirs and reduce excess water production during hydrocarbon recovery. A recent gel process uses the preformed particle gels (PPGs) to overcome distinct drawbacks inherent in in-situ gelation systems, i.e. lack of control on gelation time, uncertain gelling due to shear degradation, chromatographic fractionation or change of gel compositions, and dilution by formation water. This paper describes the results of PPG injection in both fracture and sandpack models where experimental results were used to develop and validate mechanistic models to design and optimize the flowing gel injection for conformance control processes. Crucial gel properties, such as in-situ rheology and swelling ratio in addition to oil recoveries were investigated. Water and oil permeability reduction factors were measured and modeled as a function of gel rheological properties, rock permeability, and flow rate. The PPG transport models were successfully implemented in a reservoir simulator and validated against the laboratory experiments.